PEMBELAJARAN JARAK JAUH Pendidikan Era Revolusi Indrusti 4.0: Studi Pendidikan Dan Pembelajaran Jarak Jauh Di Aceh - murtadha murtadha (Enlightenment Publishing, 2023)
Distance Learning (distance learning, distance education) is interpreted as a learning method that is held separately between teachers and students physically. This separation is the distance of transactions that occur in the learning process so that a formula is needed to bridge the boundaries of transactions in learning because the distance of transactions results in different perceptions of the concepts conveyed. Distance Education is a formal educational activity between students and teachers who are in different locations and taught remotely without a physical classroom. To organize distance learning, students and teachers must use an interactive telecommunication system so that they can connect with each other. Long Distance Activities have the main principle of access, which relates to the desire to expand people's access to education through the provision of education based on communication and information technology, is mass, economical, and minimizes distance and time constraints. Based on the Higher Education Law number 12 of 2012, article 31 concerning Distance Education explains that it is a teaching and learning process that is carried out remotely through the use of various communication media. will provide Higher Education services to groups of people who cannot attend face-to-face or regular education; and expanding access and facilitating Higher Education services in Education and learning. organized in various forms, modes and scopes supported by learning facilities and services as well as an assessment system that guarantees the quality of graduates in accordance with the National Higher Education Standards.